2021
DOI: 10.22434/ifamr2019.0215
|View full text |Cite
|
Sign up to set email alerts
|

Exploring variability across cooperatives: economic performance of agricultural cooperatives in northern Ethiopia

Abstract: The number of agricultural cooperatives increased quickly in Ethiopia since the 1990s. While many papers studied the impact of membership of Ethiopian cooperatives, not much is known on their performance. This study takes a cooperative-level perspective which is unique in an African context. It compares the economic performance proxied by sales revenue and profit of a wide range of agricultural cooperatives in northern Ethiopia. Data were collected from 511 agricultural cooperatives in 12 districts of Tigray. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 83 publications
3
25
5
Order By: Relevance
“…It also involves improving the technical efficiency of farmers [15]. With the goal of improving production, marketing and livelihoods, cooperatives are a way to reduce high transaction costs as well as serving multiple purposes, such as increasing member income and improving productivity and product quality [16,17]. Cooperatives effectively improve the technical efficiency of members by providing support to farmers, and then promote the productivity and commercialization of small farmers [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also involves improving the technical efficiency of farmers [15]. With the goal of improving production, marketing and livelihoods, cooperatives are a way to reduce high transaction costs as well as serving multiple purposes, such as increasing member income and improving productivity and product quality [16,17]. Cooperatives effectively improve the technical efficiency of members by providing support to farmers, and then promote the productivity and commercialization of small farmers [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To overcome the constraints of smallholder agriculture, agricultural cooperatives, as an important institutional arrangement, have been formed and developed to support sustainable agricultural production and rural development in the countries where smallholder farmers usually dominate agriculture. A great number of studies focusing on Asian countries (e.g., China and India) and African countries (e.g., Ethiopia, Rwanda, and Zambia) have confirmed the important role of agricultural cooperatives in helping smallholder farmers benefit from agricultural production and marketing (Chagwiza et al, 2016;Iliopoulos, 2013;Kumar et al, 2018;Liu et al, 2019;Ma & Abdulai, 2019;Manda et al, 2020;Priscilla & Chauhan, 2019;Sebhatu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, a few studies (e.g. Barham & Chitemi 2009;Sebhatu et al 2021) have discussed group characteristics and internal dynamics, and how these affect the influences of groups. Often, the focus of studies is on whether a farmer belongs to a group, without investigating the characteristics of the different groups that farmers belong to.…”
mentioning
confidence: 99%
“…Barham and Chitemi (2009) found that groups that were characterised by maturity, strong internal institutions, good asset bases of natural capital and male dominance had better market outcomes. Sebhatu et al (2021) highlighted the importance of group total assets, membership size and occurrence of conflict among members as vital factors that influence group performance. It is difficult to monitor and enforce rules in bigger groups because of the increasing transactional cost for rule enforcement due to free-riding among members (Gezahegn et al 2019).…”
mentioning
confidence: 99%